An index to assess the extent and success of river and floodplain restoration: Recognising dynamic response trajectories and applying a process‐based approach to managing river recovery. (22nd July 2020) - Fuller, Ian C.; Death, Russell G.; Garcia, J. Horacio; Trenc, Neven; Pratt, Renae; Pitiot, Claudie; Matoš, Bojan; Ollero, Alfredo; Neverman, Andrew; Death, Amanda
Abstract: How should the success of river and floodplain restoration be assessed? What should we be restoring? We contend that the benchmark for restoration should be the river in its "natural, " that is, quasi‐equilibrium condition prior to deliberate modification. The pre‐modification condition of the river represents a quasi‐equilibrium state in which the river accommodates and adjusts to catchment water and sediment fluxes, whether in a pristine or modified catchment. The resulting assemblage of river landforms (e.g., bars, channels, backwaters) is in balance with the prevailing flood and sediment regime. Furthermore, equilibrium channel forms can adjust to changes in, for example, flood magnitude and frequency via for example, channel expansion or contraction. A restored river system is one that once was anthropogenically restricted, but now has regained capacity to adjust its form. River restoration needs understanding of the history and trajectory of pre‐modification channels, so that the "right" river type can be restored. To assess the scope and success of restoration, we propose using a natural character index (NCI). The NCI is the ratio between a parameter which describes the form and function of a river now (observed) and the same parameter measured at a point or points in time past (expected). Exemplar parameters include sinuosity, floodplain width, active channel width, bar area (at a given flow) and riparian vegetation. Measurement of these parameters utilizes a combination of aerial photos, archive maps and LiDAR‐derived terrain models, the availability of which necessarily limits and determines what parameters can be used in NCI assessment. LiDAR is a useful tool providing an opportunity to comprehend pre‐modification river and floodplain character. We illustrate the NCI concept and its potential for use in assessing restoration effects using examples from New Zealand, Spain and Croatia. The result is an index of use as a "first cut" preliminary assessment for river practitioners.